2014
DOI: 10.1016/j.ijpharm.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of amorphous ibuprofen in Upsalite, a mesoporous magnesium carbonate, as an approach to increasing the aqueous solubility of poorly soluble drugs

Abstract: One attractive approach to increase the aqueous solubility and thus the bioavailability of poorly soluble drugs is to formulate them in their amorphous state since amorphous compounds generally exhibit higher apparent solubilities than their crystalline counterparts. In the current work, mesoporous magnesium carbonate was used to stabilise the amorphous state of the model substance ibuprofen. Crystallisation of the drug was completely supressed in the formulation, resulting in both a higher apparent solubility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 42 publications
11
101
0
Order By: Relevance
“…Figure 3 shows that pure IBU was a crystalline substance with sharp distinct peaks observed at 2θ of 6.0°, 12.1°, 16.5°, 18.7°, 20.1° and 22.1°, which were in good agreement with the previous report [16]. Both S244FP and NS2 carriers were amorphous without any distinctive peak.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 3 shows that pure IBU was a crystalline substance with sharp distinct peaks observed at 2θ of 6.0°, 12.1°, 16.5°, 18.7°, 20.1° and 22.1°, which were in good agreement with the previous report [16]. Both S244FP and NS2 carriers were amorphous without any distinctive peak.…”
Section: Resultssupporting
confidence: 90%
“…In the immersion method, the porous materials are immersed into a concentrated drug solution for the adsorption of drug molecules on the walls of the pores, and then, the drug loaded mesoporous materials are recovered through different approaches, such as filtration, slow evaporation, spray drying and rotary evaporation [7]. The properties of the mesoporous carriers, including the particle size/morphology, pore diameter, total surface area and volume and surface chemistry, can affect the drug loading efficiency and release rate [3,4,6,9,10,11,12,13,14,15,16]. It has also been found that the loading procedure is a crucial factor affecting the drug loading efficiency, packing of the drug molecules in the pores and thereafter the release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In our previous work, the novel mesoporous and amorphous material Upsalite ® was investigated as a phase stabilizer of amorphous ibuprofen to increase its dissolution rate. [11][12][13][14] Upsalite ® consists of magnesium carbonate (MgCO 3 ) that is "generally recognized as safe" by the FDA. It has a large specific surface area (typically 300-800 cm 2 /g) and a narrow pore-size distribution (usually 6-8 nm), and these material properties have been associated with high loading of ibuprofen (30%) and suppressed crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs with poor aqueous solubility subsequently have low bioavailability, which can limit their therapeutic efficacy (Zhang et al, 2014). In this study, we shed more light on the interactions between poorly soluble drug and the carrier metrics, the equilibrium and the kinetic adsorption models of (Ibu) on CD-grafted chitosan polymer were investigated.…”
Section: Introductionmentioning
confidence: 99%